Common Reactions of Furfural to scalable processes of Residual Biomass (2020)
Energy and the environment will always play key roles in society. The climate emergency cannot be ruled out to enable the transition for a clean energy future. Currently, non-renewable energy resources are declining, therefore is important to continuously explore renewable resources. Biomass is a renewable resource that can be applied to reduce climate changes and to accomplhish emission policies. Cellulose is the most abundant type of biomass worldwide, which can be transformed into biofuels and potential building block platform molecules (e.g furfural) throughout biological or chemical methods. Furfural can be synthetized from cellulose using hydrolysis and dehydration reactions. Furfural has a furan ring and carbonyl functional group which makes it an important intermediary to produce higher value-added molecules at  industrial level. These molecules include gasoline, diesel and jet fuel. However, furfural can also be transformed by hydrogenation, oxidation, decarboxylation and condensation reactions. The selective hydrogenation of furfural produces furfuryl alcohol, an important industrial compound, which is widely employed in the production of resins, fibers, and is considered an essential product for pharmaceutical applications. On the other hand, the oxidation of furfural produces furoic acid which is appliedin the agrochemical industry, where it is commonly transformed to furoyl chloride which is finally  used in the production of drugs and insecticides. The oxidation and reduction of furfural can carry out through heterogeneous and homogeneous catalysis, and biocatalysis.  Selectivity is an important issue in furfural hydrogenation and oxidation reactions since different products can be obtained by using monometallic or bimetallic catalysts and/or different catalyst supports. In biocatalysis approach, different enzymes, complete cells, tools of modern biotechnology, DNA sequencing, regulation of metabolic networks, overexpression of genes that encode enzymes of interest and optimization of the cellular properties of the microorganism are used. Herein, a review on the current status of furfuryl alcohol and furoic acid production from furfural by heterogeneous catalysis and biocatalysis has been studied. The stability, selectivity and activity of catalystsalong with the different furfural oxidation and reduction conditions have been pointed out. Additionally, the main enzymes, microorganisms and mechanism involved in the furfural degradation process have also been discussed.